Arts and Crafts: For the Promotion of an Ecosystem of Culture, Knowledge, and Entrepreneurship - Torres-Zapata, I (Common Ground Research Networks, 2020)
Handicrafts, arts, and crafts have been an image of cultures and places, promoting the tradition of the handmade, which has been handed down from generation to generation. Nevertheless, as a result of the increased use of technology and globalization, this important sector is dying out. This phenomenon is observed in different countries and cultures, especially in those where mass products are more valued. This is how the phenomenon of the extinction of handicrafts, arts, and crafts (HAC), is presented as a social transformation that requires greater understanding and analysis from an interdisciplinary approach. This article proposes to extract, from the members of three different cultures-Chile, Spain, and Italy-the possible common elements in this process of extinction that have arisen in these countries, through the methodology of Grounded Theory. Open interviews with institutions, artisans, and professionals linked to the arts and crafts sector, which have made their knowledge and tradition a way of life and also a way of income generation. According to the findings of this research, common elements emerge from these three countries that explain the phenomenon of the extinction of the HAC. Nevertheless, at the same time it is seen that the survival of the sector is due in part to the promotion of cultural entrepreneurship, the cultural project, and cultural education. All these elements converge on the need to generate interdisciplinary education as material for the resurgence of this sector, through the promotion of "cultural entrepreneurship." Furthermore, the so-called creative industries encourage reinstituting these traditions to place them in a contemporary context, at the same time taking advantage of the exponential growth of technology. The union of all these elements will close gaps and unite areas of culture, territory, creativity, and business, improving the participation of future entrepreneurs and promoting public policies that help to reverse the negative effects of the HAC extinction phenomena so far experienced. © Common Ground Research Networks, Mariá José Araya León, Isabel E. Torres Zapata, Fernanda N. Ramírez, All Rights Reserved.